The Panchromatic Hubble Andromeda Treasury: III. Measuring ages and masses of partially resolved stellar clusters - Beerman, Lori C.; Gouliermis, Dimitrios A.; Rix, Hans-Walter (The astrophysical journal, 2012)
The apparent age and mass of a stellar cluster can be strongly affected by stochastic sampling of the stellar initial mass function (IMF), when inferred from the integrated color of low-mass clusters ([http://ej.iop.org/icons/Entities/lsim.gif] lsim 10 4 M ☉ ). We use simulated star clusters to show that these effects are minimized when the brightest, rapidly evolving stars in a cluster can be resolved, and the light of the fainter, more numerous unresolved stars can be analyzed separately. When comparing the light from the less luminous cluster members to models of unresolved light, more accurate age estimates can be obtained than when analyzing the integrated light from the entire cluster under the assumption that the IMF is fully populated. We show the success of this technique first using simulated clusters, and then with a stellar cluster in M31. This method represents one way of accounting for the discrete, stochastic sampling of the stellar IMF in less massive clusters and can be leveraged in studies of clusters throughout the Local Group and other nearby galaxies.